2010
DOI: 10.1182/blood-2009-08-237834
|View full text |Cite
|
Sign up to set email alerts
|

CLEC-2 activates Syk through dimerization

Abstract: The C-type lectin receptor CLEC-2 activates platelets through Src and Syk tyrosine kinases, leading to tyrosine phosphorylation of downstream adapter proteins and effector enzymes, including phospholipase-C ␥2. Signaling is initiated through phosphorylation of a single conserved tyrosine located in a YxxL sequence in the CLEC-2 cytosolic tail. The signaling pathway used by CLEC-2 shares many similarities with that used by receptors that have 1 or more copies of an immunoreceptor tyrosine-based activation motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 36 publications
6
148
1
1
Order By: Relevance
“…CLEC-2, a C-type lectin receptor, has been shown to signal independently of the FcR␥ chain in platelets (16,34). The presence of Syk phosphorylation (38) and detectable levels of Lat phosphorylation in platelets activated with fucoidan ( Fig. 3) suggested that CLEC-2 (39) may be a possible receptor candidate for fucoidan on platelets.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…CLEC-2, a C-type lectin receptor, has been shown to signal independently of the FcR␥ chain in platelets (16,34). The presence of Syk phosphorylation (38) and detectable levels of Lat phosphorylation in platelets activated with fucoidan ( Fig. 3) suggested that CLEC-2 (39) may be a possible receptor candidate for fucoidan on platelets.…”
Section: Resultsmentioning
confidence: 97%
“…2-4). Downstream of the GPVI or CLEC-2 receptor, Syk kinase has been shown to play an important role in activating other effectors, which ultimately leads to the activation of ␣IIb␤3 (38,44). Inhibition of Syk following GPVI stimulation shuts down all functional responses.…”
Section: Discussionmentioning
confidence: 99%
“…Active PLC-2 hydrolyzes membrane bound polyphosphoinositides, notably phosphatidylinositol 4,5-bisphosphate, to form soluble inositol 1,4,5-trisphosphate, which releases cytosolic calcium from the internal stores, and membrane-bound 1,2-diacylglycerol, which activates protein kinase C. Signals are also sent to phosphoinositide 3-kinase, generating D3-containing polyphosphoinositides (Pasquet et al, 1999). CLEC-2 only contains a single YXXL motif but appears to be active as a dimer (Watson et al, 2009;Hughes et al, 2010) and signals through many of the same components as GPVI because platelets lacking LAT, SLP-76, or PLC-2 are not receptive to ligation of this receptor with rhodocytin (SuzukiInoue et al, 2006;Fuller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…65 Unlike the FcR g-chain and FcgRIIA that contain tandem tyrosine residues in their ITAMs, CLEC-2 contains a single tyrosine residue in its hemi-ITAM that binds a single Syk SH2 domain with low affinity when phosphorylated. 66 Tandem phosphorylated CLEC-2 receptors are thus required to provide a high-affinity docking site for a single Syk molecule. 66 Rhodocytinmediated tyrosine phosphorylation of CLEC-2 and downstream signaling proteins is inhibited in human platelets treated with PP2, which suggests an important role of SFKs in initiating CLEC-2 signaling.…”
Section: Distinct Roles Of Sfks In Itam-and Hemi-itam-containing Recementioning
confidence: 99%
“…66 Tandem phosphorylated CLEC-2 receptors are thus required to provide a high-affinity docking site for a single Syk molecule. 66 Rhodocytinmediated tyrosine phosphorylation of CLEC-2 and downstream signaling proteins is inhibited in human platelets treated with PP2, which suggests an important role of SFKs in initiating CLEC-2 signaling. 67 However, phosphorylation of the CLEC-2 is normal in rhodocytin-stimulated Src-, Lyn-and Fyn-deficient mouse platelets.…”
Section: Distinct Roles Of Sfks In Itam-and Hemi-itam-containing Recementioning
confidence: 99%